Post-traumatic stress following total hysterectomy for benign disease: an observational prospective study. (2nd January 2022) - Casarin, Jvan; Ielmini, Marta; Cromi, Antonella; Laganà, Antonio Simone; Poloni, Nicola; Callegari, Camilla; Ghezzi, Fabio
Abstract: Purpose: Over the last decade, there has been growing interest in the psychophysical integrity of surgical patients in the context of healthcare events. In the present study, we aimed to evaluate the incidence rate of postoperative distress symptoms, namely post-traumatic stress disorder (PTSD), following total hysterectomy for benign disease. We also investigated possible associations between sociodemographic characteristics, clinical outcomes, anxiety, depression, and PTSD. Methods: We prospectively enrolled 100 consecutive patients who underwent total hysterectomy for benign disease between 01/01/2019 and 15/04/2019. Demographic and surgical-related characteristics have been registered. The Hospital Anxiety and Depression Scale (HADS) questionnaire was administered preoperatively (Time1), postoperatively (Time2), and at follow-up clinical evaluation, between two and three months after surgery (Time3). PTSD was defined based on the results of the Post-traumatic Stress Disorder Checklist for DSM-5 (PCL-5) at Time3. Results: At Time3, the median PCL-5 score was 12, 8 (0–70), and 16.4% of patients had PTSD symptoms (PCL-5 > 33). No correlation between sociodemographic or gynecologic characteristics and PTSD was detected. A significant association between depression (HADS > 8) at Time2 ( p = 0.002) and Time3 ( p < 0.001) and PTSD symptoms was shown. Conclusion: Hysterectomy for benign disease is associated with a non-negligible risk of PTDS; the use of the HADS questionnaires might be useful to select patients who might benefit from dedicated psychological support.